THYROID DYSFUNCTION IN PATIENTS OF REPRODUCTIVE AGE GROUP PRESENTING WITH ABNORMAL UTERINE BLEEDING (The Research of Medical Science Review, 2025)
Background: Abnormal uterine bleeding (AUB) significantly affects women’s health, with thyroid dysfunction being a potential underlying cause. However, controversy exists regarding its frequency in AUB. This study aimed to clarify the prevalence of thyroid dysfunction in such cases. Objective: To determine the frequency of thyroid dysfunction in patients of reproductive age group presenting with AUB. Duration: Three months w.e.f 16-10-2024 to 15-03-2025 Methodology: After receiving approval from the Ethical Committee of Ghurki Trust Teaching Hospital, 151 women of reproductive age presenting with AUB were enrolled from the outpatient ward. Informed written consent was taken, and participants underwent a demographic examination and thyroid profile tests (T3, T4, TSH). Data was collected using a predesigned questionnaire and analyzed using SPSS version 26.0. Results: The study included 151 participants with a mean age of 31.15±7.71 years and mean BMI of 26.57±3.55 kg/m². Participants were categorized by age, parity, and types AUB. Thyroid dysfunction was present in 31.1% of participants. Stratification showed no significant differences in thyroid dysfunction across age, parity, BMI or AUB types. Conclusion: In conclusion, thyroid dysfunction was present in 31.1% of participants with abnormal uterine bleeding. Despite no significant differences in stratification, this highlights the importance of routine thyroid screening in this population.